Patient-reported outcome measures suitable for quality of life/well-being assessment in multisectoral, multinational and multiperson mental health economic evaluations - Łaszewska, A; Helter, TM; Nagel, A; Perić, N; Simon, J (BMJ Publishing Group, 2021)
Question: The aim was to systematically collate and synthesise existing, publicly available patient-reported outcome measure (PROM) information suitable for quality of life (QOL)/well-being measurement in mental health economic evaluations, with specific focus on their applicability in multisectoral, multinational, multiperson economic evaluations and to develop an electronic PROM compendium with meta-data. Study selection and analysis: A systematic literature search for non-disease-pecific PROMs and their versions suitable for the measurement of QOL/well-being or recovery was conducted from 2008 to February 2020. Six criteria were applied to judge their suitability in multisectoral, multinational, multiperson economic evaluations: (i) availability of separate adult and child/adolescent versions, (ii) availability of a proxy-completion option, (iii) assessing outcomes beyond health, (iv) availability of translations (≥2 language versions), (v) availability of a preference-based valuation, (vi) availability of value sets in more than one country. Findings: The final ProgrammE in Costing, resource use measurement and outcome valuation for Use in multisectoral National and International health economic evaluAtions (PECUNIA) PROM-MH Compendium includes 204 unique scales, out of which 88 are individual instruments, while the remaining 116 scales belong to 46 PROM families with more than one distinctive version. Out of the total 134 individual PROMs/PROM families, 72% have at least two language versions, 8% measure broader well-being beyond health-related QOL, 11% have preference-based valuation, with multiple country sets available for 60% of these. None of the identified PROMs met all six proposed criteria. Conclusions: The PECUNIA PROM-MH Compendium provides a unique overview of the relevant PROMs and their linked meta-data, and should be a helpful tool when choosing a suitable instrument for future mental health economic evaluations.